Practical Security Approaches Against Border Gateway Protocol (BGP) Session Hijacking Attacks and Misconfiguration Errors - Oti, Stephen Brako (2015)
A Thesis submitted to the Department of Computer Science Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirement for the Degree of MPhil Information Technology. July 2012.